2020
DOI: 10.1117/1.nph.7.1.015009
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial photobiomodulation with near-infrared light from childhood to elderliness: simulation of dosimetry

Abstract: Significance: Major depressive disorder (MDD) affects over 40 million U.S. adults in their lifetime. Transcranial photobiomodulation (t-PBM) has been shown to be effective in treating MDD, but the current treatment dosage does not account for head and brain anatomical changes due to aging. Aim: We study effective t-PBM dosage and its variations across age groups using state-of-the-art Monte Carlo simulations and age-dependent brain atlases ranging between 5 and 85 years of age. Approach: Age-dependent brain mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…shown to be involved in pathological and induced anxiety but also decision making and the processing of rewards 1,43,[45][46]70 . The gamma effects we observed had very similar latencies in the cACC and the dmPFC, whereas no effects were found in the mOFC, which is considered to include the vmPFC in the anatomical parcellations in MEG studies [85][86] . In addition, we found that larger gamma activity across the cACC and dmPFC regions was associated with greater unsigned pwPEs, and trials with larger |ε2| were more likely to be followed by a response shift, more prominently in HTA.…”
Section: Discussionmentioning
confidence: 56%
“…shown to be involved in pathological and induced anxiety but also decision making and the processing of rewards 1,43,[45][46]70 . The gamma effects we observed had very similar latencies in the cACC and the dmPFC, whereas no effects were found in the mOFC, which is considered to include the vmPFC in the anatomical parcellations in MEG studies [85][86] . In addition, we found that larger gamma activity across the cACC and dmPFC regions was associated with greater unsigned pwPEs, and trials with larger |ε2| were more likely to be followed by a response shift, more prominently in HTA.…”
Section: Discussionmentioning
confidence: 56%
“…Parallelization of diffuse reflectance (DR) MC modeling has led to better understanding of biophotonic phenomena, including optical dosimetry [33], bone injuries [34], and transcranial photobiomodulation [35,36]. In RS, recent work has demonstrated the benefit of a parallelized Raman MC model for simulation of an full Raman spectra [20,23].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to LCMV beamforming, the MEG signals were band-pass filtered between 1 and 40 Hz for the alpha and beta range and between 30 and 124 Hz for the gamma range (below the Nyquist rate at 125 Hz). Last, source estimate time courses for individual vertices were obtained for a set of cortical labels corresponding to our ROIs: anterior cingulate cortex (rostral ACC [rACC], caudal ACC [cACC]), medial OFC and lateral OFC, which include the vmPFC according to previous MEG work (Yuan et al, 2020, but see Rushworth et al, 2011 for a debate on the vmPFC delineation), dorsomedial PFC (dmPFC; label superior frontal gyrus, SFG). The representative time course per label was obtained using the “PCA flip” method in MNE-Python.…”
Section: Methodsmentioning
confidence: 99%
“…[rACC], caudal ACC [cACC]), medial OFC and lateral OFC, which include the vmPFC according to previous MEG work (Yuan et al, 2020, but see Rushworth et al, 2011 for a debate on the vmPFC delineation), dorsomedial PFC (dmPFC; label superior frontal gyrus, SFG). The representative time course per label was obtained using the "PCA flip" method in MNE-Python.…”
Section: Source Analysismentioning
confidence: 99%